2013
DOI: 10.1038/ng.2591
|View full text |Cite
|
Sign up to set email alerts
|

Exome and whole-genome sequencing of esophageal adenocarcinoma identifies recurrent driver events and mutational complexity

Abstract: The incidence of esophageal adenocarcinoma (EAC) has risen 600% over the last 30 years. With a five-year survival rate of 15%, identification of new therapeutic targets for EAC is greatly important. We analyze the mutation spectra from whole exome sequencing of 149 EAC tumors/normal pairs, 15 of which have also been subjected to whole genome sequencing. We identify a mutational signature defined by a high prevalence of A to C transversions at AA dinucleotides. Statistical analysis of exome data identified sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
744
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 684 publications
(812 citation statements)
references
References 81 publications
61
744
6
1
Order By: Relevance
“…Although TP53 mutation has a high specificity, it will not identify all patients with HGD or early cancer, since the prevalence is 70-80%. 9,11 To increase our sensitivity for detecting high-risk Barrett's patients, we propose including additional molecular biomarkers combined with clinical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although TP53 mutation has a high specificity, it will not identify all patients with HGD or early cancer, since the prevalence is 70-80%. 9,11 To increase our sensitivity for detecting high-risk Barrett's patients, we propose including additional molecular biomarkers combined with clinical factors.…”
Section: Introductionmentioning
confidence: 99%
“…2B). This identification of BRCA1 and PRKDC in EAC is striking, as these genes are involved in DNA editing and repair mechanisms, which could be explained by the high degree of genomic rearrangement and chromothriptic events seen in EAC (8,28). PRKDC was further validated as being upregulated in EAC at the protein level by IHC ( Fig.…”
Section: Network Analysis Reveals Eac Specific Coexpression Networkmentioning
confidence: 95%
“…The separation of these mutational signals can give insight into the driving forces behind tumorigenesis. For instance, a study of esophageal cancers has revealed a quite unique signature of (AA>AC) transversions making up to 29% of all substitutions in this tumor [86]. …”
Section: Box 2: Extracting Mutation Signaturesmentioning
confidence: 99%